STRATEGI BADAN AMIL ZAKAT DALAM MENDORONG PARA DOSEN MENJADI MUZAKKI DI PASAMAN - Nazaruddin, Nazaruddin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
BAZNAS carried out several strategies in encouraging the community to become mukkie. This study aims to find out the strategy carried out by Baznas Pasaman in encouraging lecturers in Pasaman to become muzakki and pay zakat through Baznas Pasaman. The research method used is a qualitative approach with the type of case study research. The results of the research show that there are 5 strategies being carried out, namely 1 getting to know the lecturer well. (2) determining common goals, (3) compiling programs (4) determining social media methods, (5) direct outreach to campuses in Pasaman